Morocco : Technical Note-Macroprudential Policy: Institutional Arrangements and Instruments. (IMF Staff Country Reports; Country Report ;, 2016)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for Morocco in the area of macroprudential policy, which can play an important role in mitigating financial stability risks in Morocco. The institutional framework is sound, but could be further strengthened. The current institutional setup comprising the Systemic Risk Surveillance and Coordination Committee provides a good framework, but remaining gaps could undermine its ability and willingness to act. Bank Al-Maghrib has recently taken important steps to advance financial stability analysis and develop a macroprudential policy framework. A risk mapping framework is now in place, a Financial Stability Report is now produced, and stress testing has been fine-tuned.